Mastering VMware Horizon 6 : unlock the advanced features and full power of VMware Horizon 6 to deliver the industry's most comprehensive end-to-end user experience /: unlock the advanced features and full power of VMware Horizon 6 to deliver the industry's most comprehensive end-to-end user experience. ([2015]) - Oven, Peter von; Coombs, Barry
No abstract available